A Century long of coral records of heavy metals in coastal water of Wakatobi Marine National Park, South East Sulawesi. Issue 1 (December 2021) - Lubis, A A; Putra, A D P; Sugiharto, U; Lalang,; Zamani, N P
Abstract: Scleractinian corals absorb heavy metals in their skeletons; therefore, corals can be used as environmental recorders due to incorporating certain metals for centuries. The research was conducted in Wakatobi Marine National Park (WMNP) using a core of massive coral Porites Sp . to determine heavy metals' concentrations and assess the possible impact on the coastal water. The sample was collected by drilling the coral vertically using a pneumatic tool. Annual banding was determined by using x-ray radiography, continued with sub-sampled from each band, and analyzed using an Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES) for heavy metals determination. Enrichment Factor (EF) and Principal Component Analysis (PCA) were applied for assessing possible impact and differentiating between the heavy metals, respectively. The concentrations of heavy metals fluctuated during the period of the year 1917 to 2016, with the average concentration were 0.55 %, 0.07 %, 2.46 ppm, 3.86 ppm, 5.70 ppm, 63.22 ppm, 0.66 ppm, 3.16 ppm, 0.66 ppm, and 42.59 ppm for Sr, Mg, Mn, Ba, Cu, K, Pb, Zn, Cr, and Al, respectively. EF for all heavy metals showed that the coastal area was at the level of very small pollution (EF<2); therefore, it can be used as baseline data.